The short-lived neon damsel Pomacentrus coelestis: implications for population dynamics. - Kingsford MJ; O'Callaghan MD; Liggins L; Gerlach G (Massey University, 2017)
Daily increments of Pomacentrus coelestis, an abundant and well-studied fish, were validated for the life of the fish and depending on the location, age-maxima were estimated to be 127-160 days on reefs separated by tens to hundreds of kilometres on the Great Barrier Reef. This contrasts with congeners and other damselfishes that live for 5 years or more. Otoliths of P. coelestis were thinner and had different patterns of banding when compared with relatively long-lived congeners. It is suggested that banding patterns in P. coelestis may be related to patterns of maturation and spawning. The consequences of a short life would have a great influence on the population dynamics of this widespread species. Further, the demographics and habitat preferences of this species suggest rapid colonization and establishment of breeding populations that would quickly change the relative abundance of sympatric fishes.
CAUL read and publish agreement
Keywords: age; age structure; coral-reef-fish; otolith; Pomacentridae; population-dynamics; 0602 Ecology; 0608 Zoology; 0704 Fisheries Sciences